A Pilot Study on Video Color Transfer: A survey of user-type opinions - Smolic, Aljosa (My University, 2020)
Multimedia software products can be used to create and edit various aspects of online media. Recently, the affordances of mobile devices and high-speed mobile data networks mean that these editing capabilities are more readily available for mobile devices enabling a broader consumer-base. However, the precise role of the user in creative practice is often neglected in favor of reporting faster, more streamlined device functionality. In this paper, we seek to identify high-level human-computer interaction issues concerning video recoloring interfaces that are driven by the needs of different user-types via a methodological and explorative process. By conducting a pilot study, we have captured both quantitative and qualitative responses that formatively explore the role of the user in video recoloring tasks carried out on mobile devices. This research presents a variety of user responses to a video recoloring application, identifying areas of future investigation for explorative practices in user interface design for video recoloring visualization. These findings present important information for researchers exploring the use of state-of-art video recoloring processes and contribute to dialogues surrounding the study of mobile technology in use.
14th International Conference on Interfaces and Human Computer Interaction, Zagreb, 2020.
PUBLISHED
Keywords: Color transfer; User study; Opinions; Usability; Creative Technologies; Computer Education/Literacy; Multimedia & Creativity; Other